2017
DOI: 10.5539/jas.v9n3p90
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Acidosis in Ruminants with a Focus on Nutrition: A Review

Abstract: An increased risk of acidosis in animals is associated with a high dry matter intake (DMI), which in turn results in the consumption of more fermentable organic matter (OM) in the rumen leading to a high production of volatile fatty acids (VFA). This is observed in lactating dairy cows and animals in a feedlot. Acute acidosis occurs when there is a severe drop in the pH of the rumen. A prolonged period when pH of in rumen remains low, it leads to sub-acute ruminal acidosis (SARA), which is a temporary imbalanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 21 publications
0
23
0
3
Order By: Relevance
“…Subacute ruminal acidosis (SARA) is an important nutritional metabolic disease in high yielding dairy cows because of the increased consumption of concentrates and highly-fermentable forages (Valente et al 2017 ). The effects of SARA include decreased dry matter intake and lower milk yield (Enemark 2008 ), ruminal pH decrease, accumulation of biogenic amines and volatile fatty acids (VFAs) (Sato 2015 ), rumen epithelial damage (McCann et al 2016 ) and laminitis (Plaizier et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subacute ruminal acidosis (SARA) is an important nutritional metabolic disease in high yielding dairy cows because of the increased consumption of concentrates and highly-fermentable forages (Valente et al 2017 ). The effects of SARA include decreased dry matter intake and lower milk yield (Enemark 2008 ), ruminal pH decrease, accumulation of biogenic amines and volatile fatty acids (VFAs) (Sato 2015 ), rumen epithelial damage (McCann et al 2016 ) and laminitis (Plaizier et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The overfeeding of high-concentrate diet decreases ruminal pH, changes ruminal microbiota structure (McCann et al 2016 ), influences ruminal fermentation characteristics and consequently leads to subacute ruminal acidosis (SARA) (Enemark 2008 ). SARA has been reported as one of the most serious nutritional diseases in high yielding dairy cows which costs a considerable economic loss all over the world each year (Valente et al 2017 ) and thus many efforts have been paid to prevent its occurrence. Interestingly, our previous study revealed that thiamine supplementation could attenuate high-concentrate diets induced SARA by decreasing ruminal lactate production and increasing ruminal pH value in rumen fluid (Pan et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oil seeds are known to have a high percentage (75% on average) of unsaturated fats (examples: oleic, linoleic, and linolenic acids) that are liquids at ambient temperature. They also have the added advantage of exerting an inhibitory effect on the growth of gram-positive bacteria (Malik et al, 2015;Valente et al, 2016Valente et al, , 2017. Excessive amounts of dietary lipids are known to have a negative…”
Section: Introductionmentioning
confidence: 99%